IMPLEMENTATION OF FLEXIBLE WORKING ARRANGEMENT (FWA) POLICY AT THE REGIONAL SECRETARIAT OF EAST JAVA PROVINCE: A PHENOMENOLOGICAL STUDY IN CRISIS SITUATIONS - Zainal Muttaqin; Jusuf Irianto; Falih Suaedi (Journal of Social Politics and Governance (JSPG), 2026)
Despite growing adoption of Flexible Working Arrangement (FWA) in public sector organisations, scholarly understanding of how civil servants subjectively experience and make meaning of FWA implementation in acute security crisis conditions — as distinct from health crises such as the COVID-19 pandemic — remains critically limited. Grounded in Edmund Husserl's descriptive phenomenology, the study employs Colaizzi's seven-step analysis method as its analytical framework. Data were gathered through in-depth semi-structured interviews with 12 purposively selected civil servants across five bureaux, supplemented by documentary analysis of the Governor's Circular Letter Number 11410 of 2025. Five major themes emerged: (1) shock and uncertainty amid crisis; (2) existential dilemma between personal safety and professional responsibility; (3) rapid adaptation through technology as a bridge for service; (4) reconceptualisation of the meaning of public service; and (5) organisational learning for future policy. The essence of the experience is formulated as existential negotiation between fear and professional commitment — a transformative journey to find meaning in service amid uncertainty. It is recommended that regional governments institutionalise crisis-responsive FWA protocols, strengthen ICT infrastructure, and develop results-based performance management systems that accommodate psychological as well as operational dimensions of flexible work.